2019
DOI: 10.1093/treephys/tpz074
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and physiological analyses reveal that Populus cathayana males adopt an energy-saving strategy to cope with phosphorus deficiency

Abstract: Dioecious trees have evolved sex-specific adaptation strategies to cope with inorganic phosphorus (Pi) limitation. Yet, little is known about the effects of Pi limitation on plant metabolism, particularly in dioecious woody plants. To identify potential gender-specific metabolites appearing in response to Pi limitation in poplars, we studied the metabolic and ionomic responses in the roots and leaves of Populus cathayana Rehd males and females exposed to a 60-day period of Pi deficiency. Besides significant de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 66 publications
(76 reference statements)
0
12
1
Order By: Relevance
“…Male individuals can adopt an energy-saving strategy when they grow in nutrient deficient conditions [43]. In our current study, however, a significant interaction between soil fertilization treatment and sex in the concentration of carbohydrates was not observed, contrary to our second hypothesis.…”
Section: Carbohydratescontrasting
confidence: 99%
“…Male individuals can adopt an energy-saving strategy when they grow in nutrient deficient conditions [43]. In our current study, however, a significant interaction between soil fertilization treatment and sex in the concentration of carbohydrates was not observed, contrary to our second hypothesis.…”
Section: Carbohydratescontrasting
confidence: 99%
“…Under P-limiting conditions, P-containing metabolites, such as nucleic acid, phospholipids and phosphorylated sugars, can be scavenged to release Pi and maintain P homeostasis in plant cells [60]. It has been shown that phosphorylated sugars are reduced by P deficiency in various plants, such as Arabidopsis [37], barley [40], white lupin (Lupinus albus) [61] and Populus cathayana [62]. Similarly, the accumulation of 6 phosphorylated sugars were decreased in P-deficient stylo roots (Fig.…”
Section: Scavenging Of Pi From P-containing Metabolites During P Defimentioning
confidence: 99%
“…Under P-limiting conditions, P-containing metabolites, such as nucleic acid, phospholipids and phosphorylated sugars, can be scavenged to release Pi and maintain P homeostasis in plant cells [59]. It has been shown that phosphorylated sugars are reduced by P deficiency in various plants, such as Arabidopsis [37], barley [40], white lupin (Lupinus albus) [60] and Populus cathayana [61]. Similarly, the accumulation of 6 phosphorylated sugars were decreased in Pdeficient stylo roots (Fig.…”
Section: Scavenging Of Pi From P-containing Metabolites During P Defimentioning
confidence: 99%